Efeitos da informação de suplementação no desempenho físico - Bagatti Júnior, Marcelo Luís [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The use of supplementation improves the performance of resistance training practitioners and in other physical activities, such as sports, through the gain of strength and muscular endurance. However, it is little known whether the increase in performance is only due to the supplement consumed, or also because the user believes in the substance's power. Therefore, the aim of the study was to verify the influence of supplementation information on physical performance. For its realization, a study was made based on bibliographical and documentary research, covering several sources such as books, scientific articles, legislation, websites, reports, theses, monographs, magazines, interviews, vídeos, etc. Afterwards, having carried out a critical analysis of the materials found and selected those that would contribute to the study, the writing of the paper began, crossing information and discussing the topic fully to support the study, contextualizing the various scenarios in which the supplementation information influenced or not the performance in physical exercise. Thus, some conclusions could be reached by analyzing the findings in the literature, such as: the performance of an individual seems to increase when he believes he is being supplemented with a substance that has a positive effect; if the individual believes he is receiving a substance that has a negative effect, his performance tends to deteriorate; a subject who receives placebo informed as an effective supplement, appears to have a perception of improvement in performance, even if the substance administered has no effect and, finally, the pain tolerance of an individual who believes he is being supplemented with an effective substance in this regard , appears to be greater when compared to a situation in which no treatment is performed.

O uso da suplementação provoca a melhora no desempenho de praticantes de musculação e de outras atividades, como as esportivas, por meio do ganho de força e resistência muscular. Entretanto, é pouco conhecido se o aumento do rendimento se da apenas pelo suplemento consumido, ou também pelo fato do usuário acreditar no poder da substância. Dessa forma, o objetivo do estudo foi verificar a influência da informação de suplementação no desempenho físico. Para sua realização, foi feito um estudo com caráter baseado na pesquisa bibliográfica e documental, abarcando diversas fontes tais como livros, artigos científicos, legislações, sites da web, reportagens, teses, monografias, revistas, entrevistas, vídeos e afins. Posteriormente, tendo realizado uma análise crítica sobre os materiais encontrados e selecionado aqueles que contribuiriam para o estudo, se deu início a redação do trabalho, cruzando informações e discutindo o tema de forma plena para dar embasamento ao estudo, contextualizando os diversos cenários em que a informação de suplementação influenciou ou não o rendimento em exercício físico. Assim, pôde-se chegar a algumas conclusões por meio da análise dos achados da literatura, como: o desempenho de um indivíduo parece aumentar quando este acredita estar sendo suplementado com substância que possui efeito positivo; se o indivíduo acreditar estar recebendo uma substância que possui efeito negativo, seu desempenho tende a piorar; um sujeito que recebe placebo informado como suplemento eficaz, aparenta ter uma percepção de melhora no desempenho, mesmo que a substância administrada não possua qualquer efeito e, por fim, a tolerância à dor de um indivíduo que acredita estar sendo suplementado com substância eficaz nesse sentido, aparenta ser maior quando comparado a uma situação em que nenhum tratamento é realizado.
Effects of supplementation information on plysical performance
Keywords: Supplementation; Performance; Resistance training; Suplementação; Desempenho; Musculação; Placebo